Sociological science. - Society for Sociological Science ([United States] : Society for Sociological Science, 2014)
Sociological Science is an open-access, online, peer-reviewed, international journal for social scientists committed to advancing a general understanding of social processes.
Description based on: Volume 1 (February 2014); title from caption (sociologicalscience.com website, viewed May 30, 2014).
Latest issue consulted: Volume 1 (May 2014) (viewed May 30, 2014).
Keywords: Sociology -- Periodicals; Sociology; Social Change; Electronic journals; Periodicals